Characterising mode I/mode II fatigue delamination growth in unidirectional fibre reinforced polymer laminates. (5th February 2015) - Al-Khudairi, O.; Hadavinia, H.; Waggott, A.; Lewis, E.; Little, C.
Highlights: Delamination fatigue behaviour of a unidirectional laminate is investigated. The threshold strain energy release rate is experimentally determined. Coefficients of Paris law for crack propagation for mode I and mode II were established. Abstract: In this paper, fatigue life estimation for delamination growth of laminated fibre reinforced polymer (FRP) composite structures in mode I and mode II based on fracture mechanics is presented. The proposed method was applied to delamination of glass/epoxy laminated composite. Both the threshold energy release rate ( Gth ) and the delamination propagation based on Paris' law were studied. The double cantilever beam (DCB) specimen for mode I and 3 points End-Notched Flexure (3ENF) specimen for mode II were used for monotonic fracture tests and the resistance GIR and GIIR as a function of delamination length were determined. For DCB tests, the fatigue onset life test was conducted and the threshold energy release rate, GIth, was found for the subcritical region. Constant amplitude, displacement controlled cyclic fatigue test for both modes was conducted and the delamination crack growth rate ( da / dN ) as a function of maximum cyclic energy release rate GImax and GIImax for DCB and 3ENF specimens were determined, respectively. From curve fitting to the experimental data, the Paris' law material constants C and m for mode I and mode II were obtained. Finally, the SEM fractography studies of delaminated surfaces of 3ENF static and fatigued specimens have been done and the different features observed on these surfaces were discussed.